Cohesive Regulation of Neural Progenitor Development by microRNA miR-26, Its Host Gene Ctdsp and Target Gene Emx2 in the Mouse Embryonic Cerebral Cortex - Zhang, Haijun; Zhang, Longbin; Sun, Tao (Frontiers in Molecular Neuroscience, 2018)
Proper proliferation and differentiation of neural progenitors in the developing cerebral cortex are critical for normal brain formation and function. Emerging evidence has shown the importance of microRNAs (miRNAs) in regulating cortical development and the etiology of neurological disorders. Here we show that miR-26 is co-expressed with its host gene Ctdsp in the mouse embryonic cortex. We demonstrate that similar to its host gene Ctdsp2, miR-26 positively regulates proliferation of neural progenitors through controlling the cell-cycle progression, by using miR-26 overexpression and sponge approaches. On the contrary, miR-26 target gene Emx2 limits expansion of cortical neural progenitors, and promotes transcription of miR-26 host gene Ctdsp. Our study suggests that miR-26, its target Emx2 and its host gene Ctdsp cohesively regulate proliferation of neural progenitors during the mouse cortical development.